Critical stress for twinning nucleation in CrCoNi-based medium and high entropy alloys - Huang, He; Li, Xiaoqing; Dong, Zhihua; Li, Wei; Huang, Shuo; Meng, Daqiao; Lai, Xinchun; Liu, Tianwei; Zhu, Shengfa; Vitos, Levente (Acta materialia, 2018)
The CrCoNi-based medium and high entropy alloys (MHEAs) have drawn much attention due to their exceptional mechanical properties at cryogenic temperatures. The twinning critical resolved shear stress (CRSS) is a fundamental parameter for evaluating the strength-ductility properties of MHEAs. Here we construct and apply an extended twinning nucleation Peierls-Nabarro (P-N) model to predict the twinning CRSSes of face-centered cubic (FCC) CrCoNi-based MHEAs. The order of the twinning CRSSes of the selected alloys is CrCoNi>CrCoNiMn>CrCoNiFe>CrCoNiFeMn and the values are 291, 277, 274 and 236 MPa, respectively. These theoretical predictions agree very well with the experimental twinning CRSSes of CrCoNi and CrCoNiFeMn accounting for 260±30 and 235±10 MPa, respectively and are perfectly consistent with the strength-ductility properties including yield stress, ultimate tensile stress and uniform elongation for fracture of the FCC CrCoNi-based MHEAs obtained at cryogenic temperatures. The present method offers a first-principle quantum-mechanical tool for optimizing and designing new MHEAs with exceptional mechanical properties. [Display omitted]